THE INFLUENCE OF LEADERSHIP, ORGANIZATIONAL CLIMATE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Indra Setiawan Hutabarat (Institute of Computer Science (IOCS), 2021)
The formulation of the problem in this study is whether leadership, organizational climate, and work motivation have an effect on employee performance at the Village Community Empowerment Service, Women's Empowerment and Child Protection in Sibolga City.This study aims to determine the influence of leadership, organizational climate, and work motivation on employee performance at the Village Community Empowerment Service, Women's Empowerment and Child Protection in Sibolga City.The sample in this study were all employees at the Village Community Empowerment Service, Women's Empowerment and Child Protection in Sibolga City, as many as 42 people. The data analysis technique in this research is multiple linear regression analysis.The results showed; Leadership partially does not have a positive and not significant effect on employee performance; Organizational climate partially positive and significant effect on employee performance; Work motivation partially positive and significant effect on employee performance.